Developments in information security and cybernetic wars - Sarfraz, Muhammad (Advances in Information Security, Privacy, and Ethics (AISPE) Book Series, 2019)
"This book focuses on cyber warfare and terrorism using examples from around the world. It covers technical aspects, management issues, social issues, and government issues that relate to cyber warfare and terrorism"--